Legal Protection for Doctors Against Refusal of Medical Ser-vices by Elderly Patients in Indonesia - Jaury Douglas Pardomuan; Abdul Kolib; Handoyo Prasetyo (International Journal of Public Health, 2025)
The growing elderly population in Indonesia has created structural challenges in the health care system. One of the crucial challenges arises in the aspect of medical decision-making that becomes increasingly complex, along with the decline in cognitive capacity, comorbidities, and chronic diseases that accompany this age group. Problems arise when elderly patients refuse medical treatment, while doctors have ethical and professional obligations to save lives. This condition is complicated by social pressure from families and collective cultural values that often ignore the right to individual autonomy. As a result, doctors are in a vulnerable position legally and ethically, especially when there are no regulations that explicitly and technically regulate the limits of professional responsibility. This study aims to analyze the form of legal protection for doctors in the face of refusal of medical action by elderly patients. The method used is normative juridical, with statutory and conceptual approaches. The results show that there are no specific rules regarding the mechanism of informed refusal, evaluation of the decision-making capacity of elderly patients, and the limits of legal responsibility of doctors. This creates legal uncertainty, even when doctors have acted according to professional standards and medical ethics. This study recommends the establishment of technical regulations that strictly regulate the procedures for refusal of medical action by elderly patients. Legal protection for doctors is not only a professional guarantee, but also an integral part of a health system that is fair, sustainable, and ensures legal certainty in modern medical practice.